1992
DOI: 10.1104/pp.99.3.1193
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Toxicity in Roots

Abstract: The inhibition of root growth by aluminum (Al) is well established, yet a unifying mechanism for Al toxicity remains unclear.The association between cell growth and endogenously generated ionic currents measured in many different systems, including plant roots, suggests that these currents may be directing growth. A vibrating voltage microelectrode system was used to measure the net ionic currents at the apex of wheat (Triticum aestivum L.) roots from Al-tolerant and Al-sensitive cultivars. We examined the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…an H ϩ /anion symport, which is in agreement with the findings of Collings et al (1992) and Ryan et al (1992) comparing two wheat cultivars differing in Al resistance; (b) enhanced respiration and thus bicarbonate production; and (c) enhanced release of organic acid anions, which at the low ambient pH in the apoplast will bind free protons. However, the release of organic anions appears unlikely to account for alkalization in the Al-sensitive cultivar, because it is well established that this will lead to Al resistance through complexation, as shown for malate in wheat (Delhaize et al, 1993b;Basu et al, 1994;Ryan et al, 1995aRyan et al, , 1995b, citrate in maize (Pellet et al, 1995), and oxalate in buckwheat (Zheng et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…an H ϩ /anion symport, which is in agreement with the findings of Collings et al (1992) and Ryan et al (1992) comparing two wheat cultivars differing in Al resistance; (b) enhanced respiration and thus bicarbonate production; and (c) enhanced release of organic acid anions, which at the low ambient pH in the apoplast will bind free protons. However, the release of organic anions appears unlikely to account for alkalization in the Al-sensitive cultivar, because it is well established that this will lead to Al resistance through complexation, as shown for malate in wheat (Delhaize et al, 1993b;Basu et al, 1994;Ryan et al, 1995aRyan et al, , 1995b, citrate in maize (Pellet et al, 1995), and oxalate in buckwheat (Zheng et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…Collings et al (1992) discussed the role of the currents observed in transducing the gravitropic stimulus from the root cap to the EZ. By removing K ϩ , Na ϩ , Ca 2ϩ , or Cl Ϫ ions from the bathing solution or by applying the Ca 2ϩ channel blocker lanthanum, they could demonstrate that the currents measured were primarily composed of protons, a finding that is in accordance with Ryan et al (1992). Ca 2ϩ influx and Cl Ϫ efflux contribute to these currents to a lesser extent (Iwabuchi et al, 1989;Ryan et al, 1992).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…High levels of toxic aluminum in the soil solution impair root growth rate, and also reduce root numbers and length, which interferes in the absorption, transportation and use of nutrients (Ca 2+ , Mg 2+ , K 2+ e P) (Foy 1978, Kochian 1995, Ryan et al 1995. Acid soils often require lime and fertilizer application to overcome nutrient deficiencies and metal toxicity, as well as to increase crop yield.…”
Section: Introductionmentioning
confidence: 99%